Fragile States: Beyond International Borders and into U.S. Communities - Debra J Bolton PhD; Francisco M Hernandez Major (Adult Education Research Conference, 2016)
“Fragile States Indicators”, used worldwide, were applied to U.S. communities with high poverty. Theories, literature and data gave rise to a model that could be applied to families and institutions with implications for adult education.
Keywords: Poverty; At-Risk Communities; Fragility; Educational Empowerment; Social Justice